Effects of different pollination methods and hot water treatment on prolonging shelflife of rockmelon (Cucumis melo L) production - Abubakar, Muhammad Muhammad (2020)
Rockmelon is gaining a lot of importance due to its high production potential as well as its high nutritive value. The presence of insect pest in rockmelon has various problems, includes direct injury to the crop and acting as vector to disease, which leads to economic losses. Use of insecticidal sprays tends to kill or repel both the pest and the natural pollinators. Many synthetic chemicals are employed today for postharvest treatment of fruit and vegetables throughout the world, but the fungicidal residues often represent a major threat to human life. The present study was conducted to determine (1) the effect of different pollination methods on rockmelon production, (2) to assess the effect of insecticide on honeybee and (3) to evaluate the effect of postharvest hot water treatments in prolonging the shelf-life of differently pollinated rockmelon. The experiments were conducted at Field 10, Faculty of Agriculture, Universiti Putra Malaysia and Laboratory B, Department of Crop Science, Faculty of Agriculture. The rockmelon was planted in rain shelter and open shelter systems. The first experiment was a 3×2 factorial (pollination methods and insecticides application) and was laid out in a nested design in three replications. The plants were pollinated using three different pollination methods, namely; natural, honeybee, and handpollination; and treated with and without insecticide. The second experiment involved different dipping time and differently pollinated rockmelon with 2×4 factorial laid in a complete randomized design (CRD) with four replications. The experiment is carried out on differently pollinated fruits which are (1) hand pollinated fruits and (2) honeybee pollinated fruits, hot water treatment at 55℃ was also examined in different dipping time periods of 0 minute (control), 1 minute, 2 minute, and 3 minutes. The result of first experiment shows that honeybee pollination is better compared to other pollination methods with having higher plant (192.83 cm), more male flower (58.3) and female flower (7.5), higher sex ratio (11.5), longer days of flowering (27.66), more number of fruit (5.6) and fruit weight (933.33 g). For insecticide and no-insecticide treatments, the result shows the best combination is the insecticide-treated plots having a higher number of the female flower (6.55) and sex ratio (10.22) compared with no-insecticide. The postharvest treatment shows that hot water treatment (55℃) prolongs the shelf life of rockmelon fruits with 2 minutes has the lowest weight loss of 11.9%, while the 1- minute treatment has highest firmed fruit (6.33 N), brix index (8.0 °Brix), juice content (79.88 %), larger rind thickness (3.2 mm) and the best appearance (3.75). On the Fusarium disease severity, the 2 minutes treatment has the least infestation of 1.0 scale compared to control treatment. However, the regression result shows that with longer dipping time, it will lower the quality of fruit. At 3 minutes dipping time, it has increased the weight loss, decreases the firmness, reduction in juice and appearance compared to 1 minute and 2-minute dipping. The observations also show that honey bee pollinated rock melon is capable of retaining the fruit quality within the three weeks of storage than the hand-pollinated fruits.